2018
DOI: 10.1136/oemed-2017-104744
|View full text |Cite|
|
Sign up to set email alerts
|

Incident CTS in a large pooled cohort study: associations obtained by a Job Exposure Matrix versus associations obtained from observed exposures

Abstract: BackgroundThere is growing use of a job exposure matrix (JEM) to provide exposure estimates in studies of work-related musculoskeletal disorders; few studies have examined the validity of such estimates, nor did compare associations obtained with a JEM with those obtained using other exposures.ObjectiveThis study estimated upper extremity exposures using a JEM derived from a publicly available data set (Occupational Network, O*NET), and compared exposure-disease associations for incident carpal tunnel syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…However, JEMs can be useful to the study of a wide range of health outcomes. There has been recent interest in applying JEMs to study the effects of workplace physical demands on musculoskeletal disorders, pregnancy outcomes, hernias, and cardiovascular disease . Such job‐related data can be obtained through The Occupational Information Network (O*NET) provided by the U.S. Department of Labor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, JEMs can be useful to the study of a wide range of health outcomes. There has been recent interest in applying JEMs to study the effects of workplace physical demands on musculoskeletal disorders, pregnancy outcomes, hernias, and cardiovascular disease . Such job‐related data can be obtained through The Occupational Information Network (O*NET) provided by the U.S. Department of Labor.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have used O*NET‐based physical exposure estimates to evaluate relationships between workplace exposures and chronic disease outcomes . One recent study showed the reliability of some O*NET‐based force and repetition variables of the hand and wrist compared to similar directly observed measures, and demonstrated their ability to predict incident carpal tunnel syndrome …”
Section: Introductionmentioning
confidence: 99%
“…Solovieva et al validated a gender‐specific JEM for workplace psychosocial factors in the study of depression and low back pain. For physical exposures, Dale et al, compared exposure‐outcome associations for the incident of carpal tunnel syndrome using a JEM created from American O*NET physical demands data and directly observed physical work exposures in a large American worker cohort. In Dale et al, effect sizes of exposures categorized by ergonomic dimension (eg, force intensity, repetition, duration) were similar between O*NET JEM values and direct observation, however, the precision of the exposure‐outcome associations using JEM estimates was lower based on wider 95% confidence intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The latter aspect of JEM validity is particularly important when occupational codes are retrieved from national registers, without occupational research as the primary objective. While the validity of exposures assigned by JEM has been examined in a number of publications (8)(9)(10)(11)(12)(13), the validity of the job titles and occupational codes per se has seldom been examined (7,14). Incorrect occupational codes in registers may be the result of erroneous reporting from the primary sources (eg, tax agents, companies) and -if classification systems have changed over time -errors in translation from one classification system to another.…”
mentioning
confidence: 99%